An upper echelons perspective on information technology business value - José Fernando López-Mu\~noz; Alejandro Escribá-Esteve (European Research on Management and Business Economics (ERMBE), 2017)
This paper argues that information technology (IT) outcomes are more valuable to companies when their top management team (TMT) moves from flirting with IT to marriage. Previous research has demonstrated an association between top management support (TMS) and IT value. We extend the concept of TMS with the imbrication metaphor to define the construct of TMT-IT imbrication, which allows us to account for a tighter and continuous entwining of the TMT and IT to create IT value. Our definition of the TMT-IT imbrication construct embraces four dimensions: involvement, participation, attention, and use. In addition, with the support of upper echelons (UE) theory, we explore certain managerial traits, competences, and team processes that may be antecedents of this imbrication. As a result, our work provides a variance model and various propositions rooted in the logic of UE that contribute to research on IT business value.
Keywords: M15; O33; G34; 650; IT value; Top management support; Upper echelons; Imbrication